2020
DOI: 10.3390/molecules25051171
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and In Vivo Effects of Flavonoids on Peripheral Neuropathic Pain

Abstract: Neuropathic pain is a common symptom and is associated with an impaired quality of life. It is caused by the lesion or disease of the somatosensory system. Neuropathic pain syndromes can be subdivided into two categories: central and peripheral neuropathic pain. The present review highlights the peripheral neuropathic models, including spared nerve injury, spinal nerve ligation, partial sciatic nerve injury, diabetes-induced neuropathy, chemotherapy-induced neuropathy, chronic constriction injury, and related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 178 publications
(261 reference statements)
0
33
0
1
Order By: Relevance
“…Moreover, kaempferol decreased advanced glycation end products and epigallocatechin gallate (EGCG) causes a reduction of 8-hydroxy-2-deoxyguanosine, which is considered as the major form of free radical-mediated oxidative stress in the nucleus and mitochondria (Valavanidis et al, 2009). It has also been found that in the diabetic animal model, genistein and naringenin raised nerve growth factor (NGF) in sciatic nerves (Basu and Basu, 2020). Therefore, NGF servesas the survival and life maintenance of the neurons.…”
Section: Effect Of Flavonoids On Diabetic Neuropathymentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, kaempferol decreased advanced glycation end products and epigallocatechin gallate (EGCG) causes a reduction of 8-hydroxy-2-deoxyguanosine, which is considered as the major form of free radical-mediated oxidative stress in the nucleus and mitochondria (Valavanidis et al, 2009). It has also been found that in the diabetic animal model, genistein and naringenin raised nerve growth factor (NGF) in sciatic nerves (Basu and Basu, 2020). Therefore, NGF servesas the survival and life maintenance of the neurons.…”
Section: Effect Of Flavonoids On Diabetic Neuropathymentioning
confidence: 99%
“…Conversely, these treatments cause a 30-50% decline in pain and are frequently restricted owing to their noticeable adverse effects, with dominant sedative action. Nowadays, natural products like plant secondary metabolites are widely used to treat several chronic diseases due to their limited adverse effects as well as high efficacy (Uddin et al, 2018bBegum et al, 2019;Samsuzzaman et al, 2019;Thangapandiyan et al, 2019;Basu and Basu, 2020). Flavonoids are a broad group of secondary metabolites, extensively found in many fruits, vegetables, wine, cocoa, and tea (Chun et al, 2007;Egert and Rimbach, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Нейропатичний біль виникає внаслідок прямого пошкодження або захворювання, що впливає на соматосенсорну систему, яка складається з периферичних волокон (мієлінізованих A та A і немієлінізованих C) і центральних нейронів [8]. Часто цей біль пов'язаний із травмою або дисфункцією периферичної нервової системи, яка врешті-решт впливає на центральну нервову систему (ЦНС).…”
Section: огляд / Reviewunclassified
“…The International Association for the Study of Pain (IASP) describes pain as "an unpleasant sensory and emotional experience that is associated with real or probable tissue damage, as defined in rapports of such injury" [1]. Although it is easy to conceptualize pain as a homogeneous entity, in reality there are several different types, each with distinct neurobiological and pathophysiological mechanisms.…”
Section: Introductionmentioning
confidence: 99%